Endoscopic Determination of Various Causes of Upper Gastrointestinal Bleeding - Maham Abdaal, Numan Ghafoor, Isma Akram, Muhammad Usman, Saqib Hussain, Mehdi Naqvi (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the various causes of upper gastrointestinal bleeding through endoscopic method. Study design: Descriptive observational study Place and duration of study: Department of Medicine, SKZB, CMH Muzaffarabad from 1st January 2021 to 30th June 2022. Methodology: Ninety patients of upper gastrointestinal bleeding which were clinically and endoscopically confirmed of their state and between <25 to >66 years of age were included. Endoscopy procedure was conducted using lignocaine gargling as analgesia. Grading system was utilized for scoring endoscopy results as Grade I to IV. Results: There were 52 (57.8%) males and 38(42.2%) females. The mean age of the patients was 48.5±3.3 years. It was also seen that majority of the males as well as females had esophageal varices and peptic ulcer as the main cause of UGB followed by esophagitis and gastritis. Conclusion: Esophageal varices and peptic ulcer followed by esophagitis and gastritis are the main cause of upper gastrointestinal bleeding. Key words: Causes, Upper gastrointestinal bleeding, Endoscopic method